2009
DOI: 10.1158/1078-0432.ccr-09-1143
|View full text |Cite
|
Sign up to set email alerts
|

Increased Ectonucleotidase Expression and Activity in Regulatory T Cells of Patients with Head and Neck Cancer

Abstract: Purpose: Regulatory T cell (Treg) frequency and activity are increased in cancer patients and play a major role in tumor escape. Although disease progression is favored by the presence of Treg, mechanisms used by Treg to suppress antitumor immunity are unknown. The ectonucleotidases CD39 and CD73 are expressed in Treg and convert ATP into immunosuppressive adenosine. In this study, the involvement of the adenosinergic pathway in Treg-mediated suppression in head and neck squamous cell carcinoma (HNSCC) patient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
133
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(146 citation statements)
references
References 45 publications
11
133
1
1
Order By: Relevance
“…It was reported for CD4þ T cells isolated from oropharyngeal tumors that they exert suppressive function via ectonucleotidases CD39 and CD73. 31 Interestingly, all isolated CD4þ T cells tested expressed the ectonucleotidases CD39 and CD73 on the surface whereas this is not the case for peripheral CD4þ T cells isolated from a healthy control (Fig. 5b).…”
Section: Tumor Immunologymentioning
confidence: 88%
See 2 more Smart Citations
“…It was reported for CD4þ T cells isolated from oropharyngeal tumors that they exert suppressive function via ectonucleotidases CD39 and CD73. 31 Interestingly, all isolated CD4þ T cells tested expressed the ectonucleotidases CD39 and CD73 on the surface whereas this is not the case for peripheral CD4þ T cells isolated from a healthy control (Fig. 5b).…”
Section: Tumor Immunologymentioning
confidence: 88%
“…The expression of CD39 and CD73 has been found on CD4þ T cells as well as on the great majority of regulatory T cells in HNSCC, and has been implicated as a mechanism for T cell suppression. 31 Analyses of these markers on the isolated T cell clones revealed that all CD4þ T-cell clones highly expressed CD39 and CD73 at the cell surface in resting state, but these included CD4 helper T cells that were not suppressive in a classical suppression assay. Notably, also influenza virus-specific CD4þ helper T cells and regulatory T cells that were isolated from PBMC cultures 40 express similar high levels of CD39 and CD73 (unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 In cancer, ADO is viewed as a pro-tumor factor which suppresses antitumor functions of Teff and promotes functions of suppressor cells (Treg and MDSC). 11,12 Generally, B cells are viewed as promoters of T-cell activation and proliferation. However, recent studies identified a small subset of CD19 C CD25 C circulating B cells that can suppress functions of other lymphocytes.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 These cells suppress functions of other immune cells in the microenvironment by mechanisms that might be cell contact dependent or might involve the production of inhibitory cytokines or adenosine. [43][44][45][46] Recently, a potent proinflammatory T-cell subset, IL-17-producing T H 17 cells, were observed among CD4 + cells in patients with ovarian carcinoma. The presence of these cells was significantly correlated to enhanced survival in these patients and was found to inversely correlate with the number of FOXP3 + Treg cells.…”
mentioning
confidence: 99%